The Impact of Practicing Servant Leadership Behaviors on Organizational Loyalty in Government Ministries in the Hashemite Kingdom of Jordan - Al-Khasawneh, Anis S.; Nusair, Osama Ahmad Sami (Jordan Journal of Business Administration, 2025)
This study aims to explore the impact of practicing servant leadership principles on organizational loyalty within government ministries in the Hashemite Kingdom of Jordan. Utilizing surveys distributed to 500 employees across 10 different ministries, the response rate was 92.8%. The findings revealed high levels of servant leadership and organizational commitment, indicating a significant positive effect of servant leadership, particularly through focusing on employees’ well-being and fairness in treatment, on enhancing organizational commitment. Conversely, aspects, such as credibility, ethical treatment, and humility, did not show a significant impact on organizational commitment. The study recommends revisiting the criteria for selecting governmental leaders to include skills that promote servant leadership and offering specialized training programs to develop these skills. Additionally, the study suggests improving benefits and incentives to strengthen the sense of belonging. This research contributes valuable insights into the effect of servant leadership on organizational loyalty, emphasizing the importance of developing effective leadership styles in the public sector.